Building students' creative characters through the Pancasila student profile strengthening project activities at SMPN 49 Palembang - Fadia Marchelliana Haryanitansyah; Umi Chotimah (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effectiveness of the Pancasila Student Profile Strengthening Project in building the creative character of students at SMPN 49 Palembang. This study uses a quantitative approach with a descriptive method. The population in this study is all students of SMPN 49 Palembang with a total of 257 students with a sample of 152 people. In this study, the sample was taken using a purposive sampling technique of propostionate stratified random sampling with the basis of a theory developed by Isaac and Michael. Data collection techniques use dokumentation, questionnaires, and interviews. Based on data analysis and discussion, it was concluded that the effectiveness of the Pancasila Student Profile Strengthening Project in building the creative character of students at SMPN 49 Palembang was categorized as moderate. This is known based on the results of the questionnaire data, namely as many as 9 (5.95%) respondents have a relatively not good level of effectiveness, 105 (69.08%) respondents have a relatively pretty good level of effectiveness, and as many as 38 (50%) respondents have a relatively good effectiveness category.